DIGITAL LITERACY COMPETENCES IN IMPROVING THE PROBLEM-SOLVING SKILLS IN FACING THE INDUSTRIAL REVOLUTION 4.0 - Nining Harnani; Dodi Tisna Amijaya; Luthfi Setiadiwibawa (Universitas Padjadjaran, 2021)
This study aims to determine student’s digital literacy competences in improving the problem-solving skills in facing the era of Industrial Revolution 4.0, which is conducted on students at several state and private universities in Bandung. This study is expected to contribute to determining student’s digital literacy competences. The methods used in this study are descriptive and verification methods, in which the data obtained will be turned into numbers, converted into percentages, and then described. The sampling technique used is purposive sampling technique, namely students at colleges and universities, both public and private in Bandung. In this study, the sample used is 300 students. The analytical tool used is regression analysis with the SPSS program. Based on the results of the study, it is found that the digital literacy competences of students in Bandung can be categorized as Good, and the problem-solving skills of students in Bandung can be categorized as Good. The results of regression analysis shown that t-count (10,902) > t-table (1,967). This means that the digital literacy competences have an effect on problem-solving skills, in which every change of 1 (one) unit in the digital literacy competences can increase the problem-solving skills by 720 units. Therefore, it can be concluded that the digital literacy competences significantly influence the problem-solving skills.